Effectiveness of warm compress and deep breathing on labor pain intensity - Triwahyuni, Anna; Marsita, Elma; Fajrin, Dessy Hidayati (Borneo Scientific Publishing, 2025)
Childbirth is a natural process that causes severe pain due to uterine contractions. If left uncontrolled, it can lead to prolonged labor and threaten the safety of the mother and fetus. This study aims to analyze the effectiveness of a combination of warm compresses and deep breathing relaxation on the intensity of labor pain during the active phase of the first stage of labor in mothers giving birth. This study used a quasi-experimental design with a two-group pretest and posttest with control group design. A total of 32 women in active phase I labor at the Karangan Community Health Center were respondents, with 16 in the experimental group receiving warm compress and deep breathing relaxation intervention, and 16 in the control group receiving deep breathing relaxation. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention. Data analysis was performed using the Paired T-Test, Wilcoxon, and Mann Whitney tests. The results showed a decrease in average pain intensity of 1.84 in the experimental group, while the control group only experienced a decrease of 1. The statistical test p-value of 0.003 (p < 0.05) showed that the combination of warm compresses and deep breathing relaxation was more effective in reducing pain intensity during active phase I labor compared to deep breathing relaxation alone. This conclusion indicates the significant effectiveness of warm compresses and deep breathing relaxation in reducing labor pain intensity.